El entorno familiar y su influencia en el desarrollo socio - afectivo, de los niños y niñas del primer grado de educación general básica de la unidad educativa Santa Teresita, y de la escuela Simón Bolívar, del cantón Celica, provincia de Loja. Periodo 2013-2014. Lineamientos propositivos - Villena Lopez, Clemencia Elizabeth (2014)
The present thesis has as a title: “THE FAMILY ENVIRONMENT AND ITS INFLUENCE IN THE BASIC GENERAL EDUCATION FIRST GRADE CHILDREN SOCIO-EMOTIONAL DEVELOPMENT “SANTA TERESITA”, AND “SIMON BOLIVAR” SCHOOLS OF CELICA CANTON, LOJA PROVINCE PERIOD 2013-2014. PROPOSITIONAL GUIDELINES. It was developed according to the academic regulations of the National University of Loja. The general objective of this research is to set how the family environment influence in the General Education First Grade Children Socio-Emotional Development “Santa Teresita”, and “Simon Bolivar” Schools of Celica canton, Loja province The methods used in this investigation were: Scientific, Synthetic, Deductive, Inductive, Descriptive, and Statistical Model. The techniques and instruments used were : the survey applied to the parents who helped to identify the types of children live “Santa Teresita”, and “Simon Bolivar” Schools of Celica canton, Loja province and an Observation guide of the emotional intelligence program that allowed to assess the socio- emotional development of children. The following results were obtained: The parent’s survey And in question No. 4, the 57 % give affection to their children, the 41% are concerned about the education of their children, and 2% support their children.in Question No. 6, 73% there is a kind of authoritative parenting, 27% a type of family environment were standards are not defined. Analyzed the results of the observation guide emotional intelligence program of the “Santa Teresa” School concluded that: 76% of the children have a positive Socio- Emotional Development and 24% negative and the “Simon Bolivar” School 81% of the children have a positive Socio- Emotional Development and 19% negative.